Pengaruh Pertumbuhan Ekonomi, Dana Alokasi Umum, PAD, Sisa Lebih Pembiayaan Anggaran, dan Luas Wilayah terhadap Belanja Modal - Alan Sepriadi; Erly Mulyani (Universitas Negeri Padang, 2021)
The purpose of this study was to determine the effect of economic growth, general allocation funds, PAD, excess budget financing and area size on capital expenditures in district / city governments in Bengkulu. The population in this study were districts / cities in Bengkulu which consisted of 10 districts / cities during the 2015-2019 period. The method used in this study was the Jenuh method with the Eviews-9 software. The results of the study indicate that partially the variables of economic growth, general allocation funds, PAD, excess budget financing and area size do not have a significant positive effect on regional spending as an independent variable on capital expenditure in regencies / cities in Bengkulu.